Imaging Analysis of Patients With Meniere's Disease Treated With Endolymphatic Sac-Mastoid Shunt Surgery - Li, Yawei; Lv, Yafeng; Hu, Na; Li, Xiaofei; Wang, Haibo; Zhang, Daogong (Frontiers in Surgery, 2022)
Objective： Endolymphatic sac surgery is effective in treating intractable Meniere’s disease (MD), but the underlying mechanism is still unknown. Our study investigated the mechanism by which endolymphatic sac-mastoid shunt (EMS) surgery is effective in treating MD by means of imaging. Methods： Nineteen patients with intractable MD underwent 3D-FLAIR MRI with a 3-Tesla unit 6 h after intravenous administration of gadolinium, before EMS and two years after the surgery. The enhanced perilymphatic space in the bilateral cochlea, vestibule, and canals was visualized and compared with that in the endolymphatic space by quantitatively scoring the scala vestibuli of the cochlea and by measuring the developing area of the vestibules quantitatively. Results：Gadolinium was present in the perilymph of the inner ear in the cochlea, vestibules, and canals of all patients. At the two-year follow-up, 14 (73.68%) patients had vertigo control. Both before and two-years after surgery, significant differences were observed in the scala vestibuli scores and developing areas of the vestibules between the affected and healthy sides. The scala vestibuli scores and the developing area of the vestibule, however, did not differ when comparing them before and after surgery. Conclusions: According to our results, endolymphatic hydrops is not significantly reduced by surgery. The mechanism by which EMS controls vertigo may be unrelated to the improvement in hydrops.